2017
DOI: 10.1007/s12544-017-0282-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of fines and rewards in the self-regulation of young drivers

Abstract: Purpose The current study examined the relations between objective and subjective measures of driving patterns, focusing on traffic violations. In addition, the study explored the potential use of rewards in order to modify driving behaviors and examined the relationship between attitudinal and demographic variables and the frequency of speeding. Method We acquired subjective and objective data on driving behaviors in a sample of 114 young student drivers in Israel's Southern region. We used a survey to acquir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…As in the current study, Merrikhpour et al [44] found that providing feedback increased compliance with speed limits, and that this positive effect was still apparent after the experiment was over, albeit to a weaker degree. Our results are also consistent with Elias [13], who demonstrated that the use of rewards could complement or possibly replace the reliance on negative sanctions to modify behavior.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As in the current study, Merrikhpour et al [44] found that providing feedback increased compliance with speed limits, and that this positive effect was still apparent after the experiment was over, albeit to a weaker degree. Our results are also consistent with Elias [13], who demonstrated that the use of rewards could complement or possibly replace the reliance on negative sanctions to modify behavior.…”
Section: Discussionsupporting
confidence: 91%
“…While sanctions reduce the number of offenses, their influence on crashes seems limited [9,11,12] and not necessarily well-maintained over the long term [9]. While numerous studies examined the effectiveness of penalties and enforcement as a tool for changing driver behavior, good or appropriate behavior is rarely highlighted in the road safety field [13].…”
Section: Introductionmentioning
confidence: 99%
“…According to the Situational Action Theory [ 49 ], people who have a tendency to commit crimes may obey the law for fear of potential legal consequences. The presence of ePolice is an incentive for drivers to do the right thing under the circumstances and yield [ 37 ]. Thus we can recommend that where space allows, wider roads to have median islands and installation of ePolice to enhance the safety of pedestrians using the crosswalk.…”
Section: Discussionmentioning
confidence: 99%
“…Approach speed of a vehicle at the crosswalk is also an important contributor to yielding or lack of it. Some studies [ 20 , 34 37 ] notes that a yield can only be possible if a driver can reasonably react to the arrival of a pedestrian, given the vehicle travel speed, distance from the conflict area, and maximum (comfortable) deceleration rate for the individual driver. However, higher rates of yielding were observed when approach speed was lower against pedestrians crossing in groups.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Elias [7] studies the relationship between the objective and subjective measures that influence traffic violations in driving behaviour. The study also examines the use of rewards as a measure to change driving behaviour in young student drivers in the southern region of Israel.…”
Section: Topical Collection On the Role Of Planning Towards Sustainabmentioning
confidence: 99%